Symposium 3: Networked learning, the Net Generation and Digital Natives: Symposium Introduction - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2010)
This symposium brings together researchers who have been investigating young people who are often described as Net Generation or Digital Native learners. The argument for the Net Generation and Digital Native theses is that there is a clear generational break and that young people have: .. not just changed incrementally from those of the past... A really big discontinuity has taken place. One might even call it a “singularity” – an event which changes things so fundamentally that there is absolutely no going back. (Prensky 2001 p 1) The research reported in this symposium has a critical stance in relation to the idea of a generational break between a new generation of young learners and older learners described as Digital Immigrants. The papers report from a variety of contexts with significant variations in both geographical and age range. The popularized argument is that there is a new generation emerging from those young people who have been ‘bathed in bits and bytes’ since birth (Palfrey & Gasser 2008, Tapscott 2009). The context of change is a powerful one as these young people have grown up in an environment infused with digital technologies and the Internet and Web have been in place all of their lives. The claim is that this material context has led to these young people developing a natural aptitude and high skill levels in relation to the new technologies. Those older people who grew up in an analogue world prior to the new technologies are portrayed as always being behind, as being immigrants to this new world and never likely to reach the levels of skill and fluency developed naturally by those who have grown up with new digital technologies. The issue is important to networked learning because these claims include specific claims about approaches to learning in the new generation. The young learner is characterized as having known qualities that apply to an entire generation. The language used about them is quite definite and contains few qualifications. For example Tapscott says this in his most recent book: In education they [the Net generation] are forcing a change in the model of pedagogy, from a teacher-focused approach based on instruction to a student-focused model based on collaboration.” (Tapscott 2009 p 11). The language is firm and direct and the claim is that like it or not a new generation is forcing change and the character of that change is student –focused and based on collaboration. Tapscott is not alone and Palfrey and Gasser have a similar message using Prensky’s term Digital Natives: In order for schools to adapt to the habits of Digital Natives and how they are processing information, educators need to accept that the mode of learning is changing rapidly in a digital age… Learning itself has undergone a transformation over the past 30 years… For Digital Natives, research is more likely to mean Google search than a trip to the library. They are more likely to check Wikipedia… Palfrey and Gasser 2008 p239) Once again the language used is highly directive. Schools need to adapt. Educators need to accept and learning has undergone a transformation. In this rhetoric there is little room for doubt or critical thinking about the direction and necessity of change. These arguments are not new but they remain influential despite a growing body of critical commentary based on empirical work with young people (for example Kennedy, Judd, Churchward, Kay & Krause 2008, Jones, Ramanau, Cross and Healing 2009) and based arguments theoretically (e.g. Bayne & Ross 2007, Bennett, Maton & Kervin 2008). Policy makers continue to adopt this kind of argument. For example the then Vice Chancellor of the Open University (UK) speaking to the university council: Most of our students, moreover, are part of what we now describe as the Net Generation. This is a generation who think IM, text and Google are verbs not applications. (Brenda Gourley VC Open University (UK), Council and Staff Address 26th September 2008) At the time the Vice Chancellor was speaking the Open University (UK) was recruiting about 20% of first level students under the age of 25, so 80% of the recruitment were older than the usual definition of the Net Generation. If further evidence is required about the persistence of these kinds of argument in the public domain a recent moral panic in the UK might provide it. Prensky has suggested that the brains of this new generation are different to previous generations (Prensky 2001a). A similar argument was advanced by Baroness Greenfield the Director of the Royal Institution in the United Kingdom and widely reported internationally. Baroness Greenfield told the House of Lords that children’s experiences on social networking sites: …are devoid of cohesive narrative and long-term significance. As a consequence, the mid-21st century mind might almost be infantilised, characterised by short attention spans, sensationalism, inability to empathise and a shaky sense of identity. (24th of February 2009 http://www.guardian.co.uk/uk/2009/feb/24/social-networking-site-changing-childrens-brains ) This argument suggests that exposure to new technologies and web services is likely to fundamentally change the brains of children and young adults. If this were true then being a digital native or a digital immigrant is a fixed product of early development and not something that can be addressed by education or training. The material basis for the existence of a Net Generation certainly exists and in many ways this has been deepened over the past 10 years. The rise of broadband connectivity to the Internet has allowed a rapid growth of new Internet and Web based services whilst mobile technologies and the convergence of the Internet and mobile telecommunications has allowed for a new portability that has also been enabled by the development of a range of devices allowing for access to the Internet on the move (Castells et al 2007). However the papers that follow paint a much more complex picture of change amongst young people. The papers show that young people at school and university use technologies in ways that are related to their purposes and exhibit a diversity that contrasts with the idea of a sharp generational change. The papers agree that there are significant age related changes but they suggest that these changes are mediated by the active appropriation of technology by young people acting purposively in influential institutional contexts.